Strategi Tobacco Control pada Ikatan Pelajar Muhammadiyah Jawa Tengah sebagai Gerakan Pencerdasan Menuju Indonesia Emas 2045 - Daei Aljanni; Radite Ranggi Ananta; Abi Umaroh; Syifa Yustiana (Suwaib Amiruddin Foundation, 2024)
Indonesia is facing a demographic bonus with peaks expected in 2030 and 2045, which is both an opportunity and a challenge for human resource development. However, this demographic bonus is threatened by the high prevalence of smoking among students, which has an impact on health and the economy. This study aims to analyze the Tobacco Control strategy implemented by the Muhammadiyah Student Association (IPM) Central Java as an intelligence movement towards Indonesia Emas 2045. The research method uses Theory of Change (ToC) and Logical Framework (Logframe) to design, monitor, and evaluate the program. The main programs include Tobacco Control Camp (TCC), Taruna Melati Thematic, and Fortasi, which are designed to educate students about the dangers of smoking, form peer mentors, and create anti-smoking communities. The results showed that the program succeeded in increasing students' awareness about the dangers of smoking, reducing smoking prevalence, and forming change agents at the community level. The expected long-term impact is a reduction in the burden of smoking-related diseases, an improvement in the quality of human resources, and a contribution to the achievement of the 2045 Golden Indonesia vision. This program serves as an effective model for other student organizations in addressing the problem of smoking among adolescents.